Model C: User acceptance of mechanisms Role of new Model (C) toward professional skills in human organizational behavior - Almekrad, Fahad (Journal of Posthumanism, 2025)
This paper is an attempts to develop new road map approach to examine (Model C* Twenty six steps established by the researcher of this paper) toward building context framework to evaluate and design mechanisms empowerment toward human resources field in organization behavior in order to introduce and demonstrate the application of acceptability to evaluate new theory as a model to be used as an important way to apply model C as a mechanism to develop new context at workplace and flexible strategic tool to facilitate and introduce new Model to contribute toward management science. Models are a key resource for organizational management. The diversity, complexity, and reusability of this resource result in the need for model management systems. The construction of a model management system involves modeling task dimension and a design level dimension. The modeling task dimension consists of model formulation, model representation, and model processing. In this paper, I identify and justify the necessary dimensions of model management research. Model ‘C’ is a systematic approach which provides twenty-six steps which enable managers to develop and empower their human resources. my argument that the MODEL C will open the door for more and further development studies.